The diversification of terpene emissions in Mediterranean oaks: lessons from a study of Quercus suber, Quercus canariensis and its hybrid Quercus afares - Welter, Saskia; Bracho-Nuñez, Araceli; Mir, Celine; Zimmer, Ina; Kesselmeier, Jürgen; Lumaret, Roselyne; Schnitzler, Jörg-Peter; Staudt, Michael (Tree Physiology, 2012)
Interspecific gene flow is common in oaks. In the Mediterranean, this process produced geographical differentiations and new species, which may have contributed to the diversification of the production of volatile terpenes in the oak species of this region. The endemic North African deciduous oak Quercus afares (Pomel) is considered to be a stabilized hybrid between the evergreen Quercus suber (L.) and the deciduous Quercus canariensis (Willd.), presumably being monoterpene and isoprene emitters, respectively. In a common garden experiment, we examined the terpene emission capacities, terpene synthase (TPS) activities and nuclear genetic markers in 52 trees of these three oak species. All but one of the Q. suber and Q. canariensis trees were found to be genetically pure, whereas most Q. afares trees possessed a mixed genotype with a predominance of Q. suber alleles. Analysis of the foliar terpene emissions and TPS activities revealed that all the Q. canariensis trees strongly produced isoprene while all the Q. suber trees were strong monoterpene producers. Quercus afares trees produced monoterpenes as well but at more variable and significantly lower rates, and with a monoterpene pattern different than that observed in Q. suber. Among 17 individuals tested, one Q. afares tree emitted only an insignificant amount of terpenes. No mixed isoprene/monoterpene emitter was detected. Our results suggest that the capacity and pattern of volatile terpene production in Algerian Q. afares populations have strongly diverged from those of its parental species and became quantitatively and qualitatively reduced, including the complete suppression of isoprene production.
10.1093/treephys/tps06910.1093/treephys/tps069
Keywords: Algerian oak; allozyme polymorphism; chemo-taxonomy; chemotype; Cork oak; isoprene synthase; isoprenoid; speciation

Modelling the drought impact on monoterpene fluxes from an evergreen Mediterranean forest canopy. (Oecologia, 2009)
In many ecosystems drought cycles are common during the growing season but their impact on volatile monoterpene emissions is unclear. Therefore, we aimed to develop and evaluate a process-based modelling approach to explore the explanatory power of likely mechanisms. The biochemically based isoprene and monoterpene emission model SIM-BIM2 has been modified and linked to a canopy model and a soil water balance model. Simulations are carried out for Quercus ilex forest sites and results are compared to measured soil water, photosynthesis, terpene-synthase activity, and monoterpene emission rates. Finally, the coupled model system is used to estimate the annual drought impact on photosynthesis and emission. The combined and adjusted vegetation model was able to simulate photosynthesis and monoterpene emission under dry and irrigated conditions with an R(2) of 0.74 and 0.52, respectively. We estimated an annual reduction of monoterpene emission of 67% for the extended and severe drought period in 2006 in the investigated Mediterranean ecosystem. It is concluded that process-based ecosystem models can provide a useful tool to investigate the involved mechanisms and to quantify the importance of specific environmental constraints.

Seasonal pattern of monoterpene synthase activities in leaves of the evergreen tree Quercus ilex - Fischbach, Robert Josef; Staudt, Michael; Zimmer, Ina; Rambal, Serge; Schnitzler, Jörg-Peter (Physiologia Plantarum, 2002)
Monoterpene synthase activities were measured in current year and 1-year-old leaves of holm oak (Quercus ilex L.). The monoterpene synthase activities of the leaves strongly changed with leaf development and leaf age. Enzyme activities increased rapidly in spring after leaf emergence, reaching maximum values in summer, which declined during the following winter period. In the next spring monoterpene synthase activities recovered in the old leaves to about one-third of values in the previous years and showed a similar seasonal variation as in young leaves. In both leaf age classes the pattern of enzymatic monoterpene formation was stable with α-pinene (33%), β-pinene (28%), and myrcene (26%) as prominent compounds followed by minor fractions of sabinene (10%) and limonene (3%). Monoterpene emission correlated with the activity of the synthetizing enzymes, indicating that monoterpene synthase activities in Q. ilex reflect the seasonal monoterpene emission potential of the leaves.
The following values have no corresponding Zotero field: publisher: Munksgaard International Publishers accession-num: 12060257
Keywords: monoterpene emissions; monoterpene synthase activities; Quercus ilex; seasonal patterns (voyant)

Seasonal pattern of monoterpene synthase activities in leaves of the evergreen tree Quercus ilex (Physiologia Plantarum, 2002)
Monoterpene synthase activities were measured in current year and 1-year-old leaves of holm oak (Quercus ilex L.). The monoterpene synthase activities of the leaves strongly changed with leaf development and leaf age. Enzyme activities increased rapidly in spring after leaf emergence, reaching maximum values in summer, which declined during the following winter period. In the next spring monoterpene synthase activities recovered in the old leaves to about one-third of values in the previous years and showed a similar seasonal variation as in young leaves. In both leaf age classes the pattern of enzymatic monoterpene formation was stable with α-pinene (33%), β-pinene (28%), and myrcene (26%) as prominent compounds followed by minor fractions of sabinene (10%) and limonene (3%). Monoterpene emission correlated with the activity of the synthetizing enzymes, indicating that monoterpene synthase activities in Q. ilex reflect the seasonal monoterpene emission potential of the leaves.